Subclass of Analytic Functions Related with Pascal Distribution Series - Amnah E. Shammaky; Basem Aref Frasin; Tamer M. Seoudy (Journal of Mathematics)
The prime purpose of this article is to derive a necessary and sufficient condition for a linear operator associated with the Pascal distribution series to be in the class TSμ,σ,δ of analytic functions. Moreover, inclusion relation and an integral operator linked to the Pascal distribution series is considered. We have also provided some results as corollaries of our theorems.